Reduced quality of life in coeliac disease is more strongly associated with depression than gastrointestinal symptoms - Sainsbury, K.; Mullan, Barbara; Sharpe, L. (Elsevier Inc., 2013)
Objective: Despite evidence indicating a heightened incidence of psychological symptoms in coeliac disease (CD), the direct link between psychological factors and quality of life (QOL) has received little attention. The purpose of this paper was to compare the relative impacts of psychological symptoms and coping to the known negative impacts of gastrointestinal symptoms and adherence to the gluten free diet (GFD) on QOL.Methods: In study 1 (N = 390), participants completed measures of QOL, psychological symptoms, coping, several indices of symptom severity, and adherence. Correlations and regression analyses were used to determine the relationships between QOL and the measured variables. Study 2 (N = 189) replicated the findings using a validated measure of current gastrointestinal symptom severity and a more comprehensive measure of coping.Results: Across both studies, poorer QOL was correlated with a higher incidence of psychological and gastrointestinal symptoms, greater reliance on maladaptive coping strategies, and poorer GFD adherence. The relationship between psychological symptoms (particularly depression) and QOL persisted when controlling for past (study 1) and current (study 2) gastrointestinal symptom severity. Psychological symptoms and GFD adherence were more strongly related to reduced QOL than gastrointestinal symptoms.Conclusion: The negative impact of psychological symptoms on QOL and adherence suggests that management in CD should include the provision of psychological coping skills, as well as purely dietetic-based strategies to minimise gastrointestinal symptoms.